2015
DOI: 10.1186/s12862-015-0414-1
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected co-linearity of Hox gene expression in an aculiferan mollusk

Abstract: BackgroundMollusca is an extremely diverse animal phylum that includes the aculiferans (worm-like aplacophorans and eight-shelled polyplacophorans) and their sister group, the conchiferans, comprising monoplacophorans, bivalves (clams, mussels), gastropods (snails, slugs), scaphopods (tusk shells) and cephalopods (squids, octopuses). Studies on mollusks have revealed an overall number of 11 Hox genes in seven out of eight molluscan “class”-level taxa, but expression data of key developmental regulators such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 64 publications
(95 reference statements)
2
76
0
Order By: Relevance
“…In the other investigated spiralians, there is only either genomic information (e.g., the mollusks L. gigantea and C. gigas) or expression analysis (e.g., the mollusks Gibbula varia and Haliotis asinina) (16,44,49,54). Most of these previous gene expression studies have demonstrated coordinated spatial or temporal expression of Hox genes along the animal's anteroposterior axis (45,46,61) or in organ systems, such the nervous system (49,54). However, the absence of studies revealing a correlation between Hox gene expression and their genomic organization in these animals hinders reconstruction of the putative mechanisms that preserve Hox clusters in Lophotrochozoa, and thus preclude generalizations about possible scenarios of Hox cluster evolution across all animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other investigated spiralians, there is only either genomic information (e.g., the mollusks L. gigantea and C. gigas) or expression analysis (e.g., the mollusks Gibbula varia and Haliotis asinina) (16,44,49,54). Most of these previous gene expression studies have demonstrated coordinated spatial or temporal expression of Hox genes along the animal's anteroposterior axis (45,46,61) or in organ systems, such the nervous system (49,54). However, the absence of studies revealing a correlation between Hox gene expression and their genomic organization in these animals hinders reconstruction of the putative mechanisms that preserve Hox clusters in Lophotrochozoa, and thus preclude generalizations about possible scenarios of Hox cluster evolution across all animals.…”
Section: Discussionmentioning
confidence: 99%
“…Although Hox gene expression is known for a handful of spiralian species (26,41,43,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), the relationship between genomic organization and expression domains is known for only three of these species, namely the annelids C. teleta and H. robusta and the planarian S. mediterranea. Consistent with their disintegrated Hox clusters, H. robusta and S. mediterranea show no temporal collinearity and only remnants of spatial collinearity (41,51,52).…”
Section: Significancementioning
confidence: 99%
“…In the light of these results, the characterisation of the Hox and ParaHox gene sets described herein, which includes four aculiferan species, provides an important prerequisite for gene expression studies, and thus research into assessing the putative functional plasticity of these genes across Mollusca. As a matter of fact, expression patterns of ten Hox (all representatives except Post-1 ) and one ParaHox gene ( Cdx ), based on the transcriptome of the polyplacophoran Acanthochitona crinita analysed herein, have recently become available from our group [41, 44]. These studies show that the Hox genes in polyplacophorans are expressed in a conserved anterior-posterior pattern along the primary (i.e., longitudinal) body axis.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the high morphological disparity, the complex life cycles, and the striking variation during the ontogeny among molluscan taxa, there is a considerable lack of molecular studies dealing with the expression of key developmental genes in this phylum. As such, only a few gene expression studies have been published, including Hox genes [3541] and ParaHox genes [4244]. These studies suggest a high plasticity and recruitment into novel functions of these genes at least in cephalopods and gastropods.…”
Section: Introductionmentioning
confidence: 99%
“…Confocal scans were conducted using a Leica TCS SP5 II confocal laser scanning microscope equipped with LAS AF, Version 2.6.0–2.6.3. A 405 nm laser was used for autofluorescence signal of the larvae in fluorescence mode and a 633 nm laser was used to scan the gene expression signal using the reflection mode (compare Jékely and Arendt, 2007; Fritsch et al., 2015). The obtained image data were further analyzed and processed with LAS AF Lite, Version 3.3.0.…”
Section: Methodsmentioning
confidence: 99%